How people come to recognise a problem and seek medical help for a person showing early signs of dementia: a systematic review and meta-ethnography - Perry-Young, Lucy; Owen, Gareth; Kelly, Susan; Owens, Christabel (SAGE, 2016)
Evidence suggests that there is usually a long delay between noticing first signs of dementia and seeking medical help. We conducted a systematic review of what people experience and how they make decisions during this time, and used a meta-ethnographic approach to synthesise the findings. Screening and quality assessment resulted in nine studies eligible for inclusion. People with dementia mainly report experiencing memory lapses, while carers focus on more subtle changes in personality. People respond to these changes in one of three ways: 1) they discount them as normal; 2) they reserve judgement as to their cause and significance, or 3) they misattribute them. Pivotal events can finally trigger help seeking. Active reflection and seeking of further evidence may lead to earlier recognition of the possibility of dementia and the need to seek help; it also reduces the risk of a pivotal event. Public education should aim to improve recognition of more subtle signs and to encourage repeated evaluation and reflection.